2021
DOI: 10.1097/cm9.0000000000001706
|View full text |Cite
|
Sign up to set email alerts
|

Current Alzheimer disease research highlights: evidence for novel risk factors

Abstract: Alzheimer disease (AD) is the most common type of dementia characterized by the progressive cognitive and social decline. Clinical drug targets have heavily focused on the amyloid hypothesis, with amyloid beta (Aβ), and tau proteins as key pathophysiologic markers of AD. However, no effective treatment has been developed so far, which prompts researchers to focus on other aspects of AD beyond Aβ, and tau proteins. Additionally, there is a mounting epidemiologic evidence that various environmental factors influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 129 publications
0
19
0
Order By: Relevance
“…This association is attributed to the microbiota-gut-brain-axis [ 8 , 9 ]. Indeed, epidemiological investigations have demonstrated associations between the composition of the gut microbiome and prevalent neurodegenerative conditions such as Alzheimer's disease [ 10 13 ] and Parkinson's disease [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This association is attributed to the microbiota-gut-brain-axis [ 8 , 9 ]. Indeed, epidemiological investigations have demonstrated associations between the composition of the gut microbiome and prevalent neurodegenerative conditions such as Alzheimer's disease [ 10 13 ] and Parkinson's disease [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several hypothesized mechanisms of the adverse effects of short sleep duration on sensory impairments. One possible explanation is that, as proposed by prior studies on sleep and brain structure, lower cortical volumes predominantly in frontal and parietal regions caused by short sleep duration was associated with hearing impairment (Brenowitz et al, 2021;Jalbrzikowski et al, 2021). Additionally, short sleep duration can give rise to chronic, systemic low-grade inflammation by impairing the hypothalamic-pituitary-adrenal (HPA) axis which is crucial in suppressing inflammatory process, so it is related to various diseases derived from disturbed metabolic clearance, such as diabetes, hypertension, and neurodegeneration (Lu et al, 2015;Ogilvie and Patel, 2018;Choe et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Sleep disturbance showed a 2.5-4.3-times higher risk for future cognitive decline while it was reported to increase the risk of dementia by 50-80% in previous studies (Shi et al, 2018;Brenowitz et al, 2021). On the molecular level, abnormal sleep duration is associated with amyloid-β accumulation (Winer et al, 2021) and sleep-disordered breathing increased tau deposition (Bubu et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of new-onset dementia gradually increased after the index stroke, reporting from 7% in the first year to 10% in the third year, and 23% in the tenth year ( Zhu et al, 2000 ). Stroke leads to intracranial hypoxia, provoking oxidative stress ( Slevin et al, 2015 ), inflammation, and microRNA alteration, which then facilitate and accelerate A-β protein accumulation ( Vijayan and Reddy, 2016 ), and finally, dementia pathogenesis ( Brenowitz et al, 2021 ). We found that the post-stroke dementia risk is highest in the relatively younger group, which appeared in the reverse direction of the stroke incidence and prevalence that increases with age ( Sedova et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%